Ligninolytic enzymes activities during biodegradation of oil palm empty fruit bunch (EFB) by locally isolated white rot fungi - Lee, Wak Ha (Universiti Malaysia Sarawak (UNIMAS), 2013)
Malaysia is one of world's largest palm oil producing countries and producing more than eighteen tonnes of crude palm oil. One of the significant problems in the palm fruit processing is managing of the wastes generated during the processes. On average, for every ton of fresh fruit bunches will produced around two hundred kg of empty fruit bunched (EFB). The abundance of EFB has created an important environmental issue such as fouling, attracting of pests and carbon dioxide and methane emissions. In order to minimize the abundant disposal of this waste and environmental problems, new applications on the use of abundant biomass as urgently required. The experimental work of this study aims to provide knowledge and infonnation on the profiling and enzyme characterization of fungi as candidate for lignin biodegradation during biodegradation of oil palm empty fruit bunch by white rot fungi. In this research, fifty five fungal isolates were successfully isolated and only ten isolates were successfully decolourised two dyes, Remazol Brilliant Blue R (RBBR) and Orange II. Cerrena sp., Athelia pellicularis (H13W) and Basidiomycetes sp. HKB30 (F9W), which gave the highest yield, were selected for further analysis in liquid medium and lignin and Mn2+-oxidizing peroxidases and laccase, activities were assayed. Lignin biodegradation trials were perfonned on the natural substrate, oil palm empty fruit bunch. The profiles and patterns of the peroxidase enzymes secreted during the lignin biodegradation process were studied. Results revealed that all three fungal isolates secretes ligninolytic enzymes during their four weeks growth period. Cerrena sp. has the highest activities towards lignin peroxidase on crush EFB recorded 9.892 U mL-1 , while Basidiomycete sp. HKB30 (F9W) is active in secreting lignin peroxidase on uncrush EFB recorded 7.627 U mL-1• As for manganese peroxidase activity, Cerrena sp. has the highest activities in the crush and uncrushed EFB, recorded 4.032 U mL-1 and 3.882 U mL-1, respectively. Overall, all these three fungal isolates exhibit the lowest enzymatic activities towards laccase. Lignin biodegradation was carried out for a period of four weeks to examine the activities of fungi in performing the degradation of lignin in EFB at one week intervals. The original lignin content in crush EFB is 28.06% were reduced by fungal pretreatments to values of 12.27%, 4.01% and 10.85% after biotreated with Cerrena sp., Basidiomycete sp. HKB30 (F9W) and Athelia pellicularis (H13W), respectively. As for the uncrushed EFB, the origina11ignin content is 35.36%. The values were reduced to 16.97%, 22.19% and 19.02% after iotreated with Cerrena sp., Basidiomycete sp. HKB30 (F9W) and Athelia pellicularis (H13W), respectively. The structure ofEFB (longitudinal section) before and after biotreated by the fungi was viewed under Scanning Electron Microscope (SEM) and it showed that the surface structure for both untreated crush and un crushed EFB consisted of firmly bound threads with smooth surface along the structure. Besides, most of the outer surface of biotreated crush and uncrush EFB seems has been altered with the presence of many holes. Further studies needs to be carried out in. their genetic manipulation studies in improving and exploiting them as biodegradation agent. Moreover, further investigations are needed to examine the lignin degradative enzymes activities particularly the oxidative enzymes that are involved especially on the characteristic, enzymology and molecular biology of the lignino1ytic system employed by the indigenous fungi. Furtliermore, the role and properties of the ligninolytic enzymes should be clarified in more detail to examine their significance for the composting processes.